2021
DOI: 10.1038/s41598-021-99022-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes from androgenic gland in Macrobrachium nipponense regulated by eyestalk ablation

Abstract: The eyestalk of crustaceans, such as Macrobrachium nipponense, contains many neurosecretory hormones affecting the process of reproduction, molting, metabolism of glucose, and other functions. In this study, important metabolic pathways and candidate genes involved in male sexual development were selected from M. nipponense. The methodology involved performing long-read and next generation transcriptome sequencing of genes from the androgenic gland after eyestalk ablation. qPCR analysis revealed that the mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 83 publications
3
18
0
Order By: Relevance
“…The genes participated in the mechanism of gonad differentiation and development and were predicted to be found in cell, cell part, cellular process, binding, and organelle in the GO assignment and the functional groups of general function prediction only, signal transduction mechanisms, posttranslational modification, protein turnover, and chaperones in the COG classification ( Figure 3 ). This finding is consistent with previous studies ( Jin et al, 2013 ; Jin B et al, 2021 ). A total of 482, 98, 240, and 208 DEGs were identified between PL5 vs. PL10, PL10 vs. PL15, PL15 vs. PL25F, and PL15 vs. PL25M, respectively.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The genes participated in the mechanism of gonad differentiation and development and were predicted to be found in cell, cell part, cellular process, binding, and organelle in the GO assignment and the functional groups of general function prediction only, signal transduction mechanisms, posttranslational modification, protein turnover, and chaperones in the COG classification ( Figure 3 ). This finding is consistent with previous studies ( Jin et al, 2013 ; Jin B et al, 2021 ). A total of 482, 98, 240, and 208 DEGs were identified between PL5 vs. PL10, PL10 vs. PL15, PL15 vs. PL25F, and PL15 vs. PL25M, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…The gonad was identified to be differentiated and developed from PL10 to PL25. Many previous studies reported that immune-related and energy-related metabolic pathways played essential roles in the gonad development in M. nipponense ( Jin et al, 2020 ; Jin B et al, 2021 ), which is consistent with this study. In addition, a total of 29 genes were considered as the strong candidate genes, involved in the mechanism of gonad differentiation and development of M. nipponense , based on gene annotation and differentially expressed pattern.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Illumina High-seq 2500 sequencing platform, which is widely used in transcriptome studies, was used to perform transcriptome profiling analysis. Previous studies have described the detailed procedures for RNA-seq and analysis ( Jin et al, 2013 ; Jin et al, 2021 ). The Trinity program (version: trinityrnaseq_r20131110) was used to assemble the clean data into non-redundant transcripts ( Grabherr et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since IAG was first identified in a decapod (the red-clawed crayfish Cherax quadricarinatus ) in 2007, it has also been found in many crustacean species such as Macrobrachium rosenbergii [ 3 ]; Macrobrachium nipponensis [ 4 , 5 ]; Penaeus monodon [ 6 ]; Fenneropenaeus chinensis [ 7 ], and Portunus pelagicus [ 8 ]. The mechanism by which IAG mediates male sexual differentiation and gonad development has been demonstrated in crustaceans [ 9 , 10 ]. For example, silencing of IAG expression with siRNA [ 11 ] and dsRNA [ 12 ] in M. rosenbergii causes functional sex reversal and stagnation of testicular spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%